Serum IL-12p40: A novel biomarker for early prediction of minimal change disease relapse following glucocorticoids therapy - Bai, Mengqiu; Zhang, Jian; Su, Xinwan; Yao, Xi; Li, Heng; Cheng, Jun; Mao, Jianhua; Li, Xiayu; Chen, Jianghua; Lin, Weiqiang (Frontiers in Medicine, 2022)
Background: Minimal change disease (MCD) has a high recurrence rate, but currently, no biomarker can predict its recurrence. To this end, this study aimed at identifying potential serum cytokines as valuable biomarkers for predicting the risk of MCD recurrence. Methods: Raybiotech 440 cytokine antibody microarray was used to detect the serum samples of 8 relapsed, 8 non-relapsed MCD patients after glucocorticoid treatment, and 8 healthy controls. The differentially expressed cytokines were confirmed by enzyme-linked immunosorbent assay (ELISA) with serum samples from 29 non-relapsed and 35 relapsed MCD patients. The study used the receiver operating characteristic (ROC) curve analysis to investigate the sensitivity and specificity of a serum biomarker for predicting the MCD relapse. Results: Serum IL-12p40 levels increased significantly in the relapsed group. The ROC curve analysis demonstrated that interleukin (IL)-12p40 was a suitable marker for the MCD-relapse diagnosis; the Area Under Curve (AUC) of IL-12p40 was 0.727 (95%CI: 0.597–0.856; P<0.01). The RNA-sequencing analysis and qPCR assay performed on the IL-12 treated mouse podocytes and the control group showed increased expression of podocyte damage genes, such as connective tissue growth factor (CTGF), matrix metallopeptidase 9 (MMP9), secreted phosphoprotein 1 (SPP1), and cyclooxygenase-2 (COX-2) in the former group. Conclusions: IL-12p40 may serve as a new biomarker for predicting the risk of MCD recurrence after glucocorticoid treatment, and it may be involved in the pathogenesis and recurrence of MCD.